2019
DOI: 10.1093/biolinnean/blz192
|View full text |Cite
|
Sign up to set email alerts
|

Within-stream phenotypic divergence in head shape of brown trout associated with invasive brook trout

Abstract: Competition with a non-native species can lead to morphological changes in native organisms induced by phenotypic plasticity, and by selection against individuals that do not adjust their morphology to the novel selection pressure. The morphological changes in native organisms are often associated with rapid behavioural responses to competition with the invader. However, knowledge of the interaction between the behaviour and morphology of native organisms competing with a non-native species remains scarce. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For example, fish with relatively short pectoral fins are better swimmers (Jones et al, 2020; Rouleau et al, 2010) and thicker caudal peduncles generate higher critical swimming speeds (Hawkins & Quinn, 1996). Brown trout that are terrestrial feeders have body forms that are streamlined, with shorter fins and longer snouts (terminal mouths) (Stelkens et al, 2012; Závorka et al, 2020). While we found the relative length of both the maxilla and snout increased in the long term, this does not match the switch to more aquatic prey, most of which cling to the benthic substrate in our system (chironomid larvae, snails, worms, amphipods).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fish with relatively short pectoral fins are better swimmers (Jones et al, 2020; Rouleau et al, 2010) and thicker caudal peduncles generate higher critical swimming speeds (Hawkins & Quinn, 1996). Brown trout that are terrestrial feeders have body forms that are streamlined, with shorter fins and longer snouts (terminal mouths) (Stelkens et al, 2012; Závorka et al, 2020). While we found the relative length of both the maxilla and snout increased in the long term, this does not match the switch to more aquatic prey, most of which cling to the benthic substrate in our system (chironomid larvae, snails, worms, amphipods).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this is first study which implemented geometric morphometrics in understanding pattern of phenotypic variation of the Dalmatian barbelgudgeon. However, geometric morphometrics has been approved as a valuable tool for uncovering subtle body shape divergence among conspecific populations of European freshwater fish underlying the influence of heterogeneous ecological environments (e.g., Bajić et al., 2018; Collin & Fumagalli, 2011, 2015; Francuski et al., 2019; Marić et al., 2015; Ramler et al., 2017; Zaccara et al., 2019; Závorka et al., 2020). Namely, it was found that differences in body shape associated with environmental factors result in a morphologically optimized phenotype for a given habitat such as a more streamline (slender) body shape and larger head of lake fish compare to stream ones (Ramler et al., 2017) as we also found.…”
Section: Discussionmentioning
confidence: 99%
“…Morphology is also shaped by foraging strategies. For example, dietary niche is associated with head and body shape in fish (Knudsen et al, 2011;Závorka et al, 2020), birds (Felice et al, 2019), and mammals (Swanson, Oliveros, & Esselstyn, 2019). Additionally, phenotypic plasticity is expected in dietary generalists, as shown in comparative commongarden experiments in stickleback minnows (Svanbäck & Schluter, 2012).…”
Section: Introductionmentioning
confidence: 99%